2014
DOI: 10.1007/s10393-014-0940-0
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Molecular Characterization of Mycobacterium tuberculosis from Humans and Cattle in Namwala District, Zambia

Abstract: Mycobacterium tuberculosis, the causative agent of tuberculosis in humans, is considered primarily a human pathogen. It has, however, been reported in a wide range of domestic and wild animals, often living in close prolonged contact with humans. Sputum samples in which acid fast bacteria were detected in smears were collected from patients at three health facilities in Namwala district, Zambia. Samples from cattle presenting gross lesions compatible with bovine tuberculosis were collected at a local abattoir … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 23 publications
5
22
2
Order By: Relevance
“…bTB exacts a tremendous global economic toll through productivity losses and disease control costs, while zoonotic transmission of M. bovis infection is a threat to human health (16). …”
Section: Genome Announcementmentioning
confidence: 99%
“…bTB exacts a tremendous global economic toll through productivity losses and disease control costs, while zoonotic transmission of M. bovis infection is a threat to human health (16). …”
Section: Genome Announcementmentioning
confidence: 99%
“…This study observed that NTM was mostly recovered from suspected TB cases whose occupation was farming. This could possibly due to overtime exposure to NTM contaminated soil and water as agriculture is the main economic activity in Namwala district (Malama et al, 2014c).In the present study NTM from humans in Namwala district were isolated and sequenced. This observation was also made in a study done in Shanghai China by Wu et al (2014).…”
Section: Discussionmentioning
confidence: 78%
“…Four sampling areas were selected and these are; Namwala central, Maala, Kabulamwanda and Chitongo. Namwala is one of the districts in Zambia with the highest TB prevalence in both animals and humans (Malama et al, 2014c;Munyeme et al, 2009). It covers an estimated total area of about 10,000 square kilometers and lies between latitudes 15 and 17°S of the equator and longitude 25 and 27°E.…”
Section: Study Sitementioning
confidence: 99%
See 1 more Smart Citation
“…An important emerging concern is not whether infection of wildlife species with MT is novel, but recent observations that MT isolates recovered from humans and members belonging to Bovidae from the same geographical area share identical spoligotypes and VNTR-MIRU profiles (Malama et al 2014;Romero et al 2011). The evidence of molecular epidemiological link provided above, has been suggested as a possible mechanism for spill backs or spill overs of MT from human TB to cattle (Malama et al 2014;Romero et al 2011;Michel et al 2013). The TB infection due to MT in antelope and gazelle identified in the present study may have been due to a number of unique situations coexisting in the sanctuary.…”
Section: Resultsmentioning
confidence: 99%